How Can Disease Control Program Contribute to Health System Strengthening in Sub-Saharan Africa : A Concept Note for Engaging in the Global Debates on Health Systems Strengthening - Damme, Wim Van; Pirard, Marjan; Assefa, Yibeltal; Van Olmen, Josefien (World Bank, Washington, DC, 2013)
Recently, there has been broad consensus in the global health community on the need for health systems strengthening (HSS) to make further progress toward the Millennium Development Goals (MDGs) in Sub-Saharan Africa. However, there is still divergence on how HSS should be framed, what HSS practically entails, and how it should be done. We set out to clarify HSS for managers of disease control programs (DCPs). In September 2000, the United Nations created a new movement in the fight against poverty: 189 countries in the General Assembly expressed their commitment to the Millennium Development Goals (MDGs) in the Millennium Declaration (World Health Organization 2004). The recognition of health as one of the key determinants of human development is translated in three health-related MDGs. MDG 4 and 5 focus respectively on children and women as priority target groups, and MDG 6 focuses on priority diseases (HIV/AIDS, malaria, and other major diseases), representing the bulk of the disease burden in low-income countries. In section two, the author first focuses on how national health systems can be understood, with their strengthening in mind, with a special focus on service delivery and on its pluralistic nature. In section three, the author uses the Anna Karenina principle to explain an approach to health systems assessment at the national level. Finally, in section four, the author develops an approach on how Disease Control Program (DCP) can contribute to Health systems Strengthening (HSS) at country level.